An experimental and numerical study on CLT panels used as infill shear walls for RC buildings retrofit. (30th June 2019) - Stazi, F.; Serpilli, M.; Maracchini, G.; Pavone, A.
Highlights: Investigation on infilled CLT shear walls for the seismic retrofit of RC frames. Diagonal compression tests showed a high shear strength of CLT panels. Numerical investigations on a CLT infilled RC frame were carried out. CLT panels have high potentialities for the strengthening of infilled RC frames. Abstract: Cross Laminated Timber (CLT) has been gaining more and more attention in research and professional fields as a sustainable and promising construction system for mid- and high-rise structures. The need of buildings higher than those usually built with CLT has pushed the research towards the development of innovative hybrid techniques in which steel framed structures incorporate CLT shear walls. This concept may be potentially extended to existing RC framed buildings, where CLT infill shear walls may constitute the base of an integrated seismic and energy retrofit. In order to investigate this potentiality, this paper presents a preliminary experimental and numerical study focused on the mechanical behavior of CLT panels used as a bracing system. In particular, diagonal compression tests on 3-ply panels have been carried out, also by reproducing a direct load transmission from the RC frame to the CLT infill. A comparison with the results of similar tests on CLT panels (with a different number of layers and thickness) and with unstrengthened and strengthened masonry infill walls has been also provided. In addition, numerical simulations have been carried out, in order to evaluate the changes in RC frame lateral response when CLT infills are added. The results have proved that CLT infills may be used as a strengthening solution, allowing RC frame to reach higher lateral stiffness and peak load values respect to masonry infills.